Venture Capital in Russia and the Global Evolution of Venture Capital - Moreva, Eugenia L. (Journal of Reviews on Global Economics, 2018)
The Topicality: The Article is to identify the perspectives for the Russian venture capital development as an integral part of its global sector. The Novelty: The Article provides the Analysis of the Russian venturing development in the lens of the Global Venturing evolution. The Practical usefulness: The Analysis results with the determination of the content transformation of the global venturing, the Russian included, and provides the basics for its further efficient governance.